Determinants of Behavioral Intention and Use Behavior in Islamic Mobile Banking Adoption - Chandra Setiawan; Eko Ganiarto; Pandu Adi Cakranegara (AIBPM Publisher, 2026)
The rapid growth of digital banking has encouraged Islamic banks to improve mobile banking services, yet the factors driving users’ intention and actual use remain inconsistent across technology adoption studies. This study aims to analyze the determinants of behavioral intention and use behavior in adopting Bank BCA Syariah mobile banking by extending the Unified Theory of Acceptance and Use of Technology (UTAUT) with trust and application quality. A quantitative cross-sectional design was applied using survey data from 139 active BCA Syariah mobile banking users. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) through SmartPLS. The results show that performance expectancy, effort expectancy, social influence, and trust do not significantly affect behavioral intention, with p-values above 0.05. Application quality has a positive and significant effect on behavioral intention (b = 0.406, p = 0.009), while facilitating conditions (b = 0.429, p 0.001) and behavioral intention (b = 0.410, p 0.001) significantly influence use behavior. Behavioral intention also partially mediates the relationship between application quality and use behavior. These findings imply that Islamic mobile banking adoption is driven mainly by application quality and facilitating conditions rather than traditional perception-based adoption factors.